(untitled) (Journal of Hama University, 2022)
Evaluate the quality of root canal fillings that made with several filling pastes by studying the voids in them when ultrasonic activation is applied or not. The research sample consisted of 60 human premolars extracted for orthodontic or periodontal reasons, divided equally into three sub-samples according to the filling paste (zinc oxide and eugenol, Ad seal sealer, Cera seal sealer), then each sub-sample was divided into two samples equally according to whether or not they were subjected to ultrasonic activation. The root canals were filled with the filling pastes approved in the study and the ultrasonic activation was applied to the filling paste using the Ufile15 ultrasonic tip 2 mm before the apical foramen and the activation was done for 20 seconds. After completion of activation, the master guttapercha cone was reinserted to the full working length, close the canal orifices with Gic and place the sample for two weeks until complete setting. Horizontal sections were performed at a distance of 2,4,6,8 mm from the apical foramen, an x40 magnification optical microscope was used, and the images were transferred to the computer to study the voids on AutoCAD software and recording the statistical results. The study found that ultrasonic activation reduced the presence of voids, the number of sections with voids and the percentage of the area of voids to the total area , while change the type of the filling pastes had no effect on the voids into the canal filling. Thus, it is recommended to use ultrasonic activation because it improves the physicochemical properties of the filling pastes and thus increases the canal sealing.